Major triterpenoids from Eucalyptus tereticornis have enhanced beneficial effects in cellular models when mixed with minor compounds present in raw extract (2021)
ABSTRACT: Obesity is a major risk factor for type 2 diabetes mellitus development and is characterized by an abnormal expansion of adipose tissue and low-grade chronic inflammation that contribute to insulin resistance. Although there are multiple treatments, most therapies can produce undesirable side effects and therefore, new and effective treatments with fewer side effects are necessary. Previously, we demonstrated that a natural extract from the leaves of Eucalyptus tereticornis (OBE100) has anti-inflammatory, hypoglycemic and hypolipidemic activities. The major compounds identified in OBE100 were three pentacyclic triterpenoids, ursolic acid, oleanolic acid, and ursolic acid lactone. Triterpenoids have shown multiples biological activities. This current study compared the biological effect produced by OBE100 with five different reconstituted mixtures of these triterpenoids. Different cell lines were used to evaluate cytotoxicity, reactive oxygen species production, inflammatory cytokine expression, glucose uptake induction, leptin and adiponectin expression, and lipid accumulation. OBE100 treatment was the most efficacious and none of the formulated triterpenoid mixtures significantly improved on this. Moreover, OBE100 was less toxic and reduced reactive oxygen species production. Our study showed that the proven beneficial properties of triterpenoids may be enhanced due to the interaction with minor secondary metabolites present in the natural extract improving their anti-inflammatory properties.